Monitoring PARKIN RBR Ubiquitin Ligase Activation States with UbFluor. Issue 3 (31st July 2018) - Foote, Peter K.; Statsyuk, Alexander V.
Abstract: PARKIN is a RING‐Between‐RING (RBR) E3 ligase, which ubiquitinates mitochondrial proteins in response to mitochondrial damage. Ser 65 of PARKIN is phosphorylated by kinase PINK1 (pPARKIN), which causes partial PARKIN activation. PINK1 also phosphorylates Ser 65 of ubiquitin (pUb), which further activates pPARKIN. Due to the lack of precise and quantitative assays to quantify the activity of PARKIN, there were many conflicting reports on the role of pUb as a PARKIN activator, whether S65E PARKIN is a true phosphomimetic of pPARKIN, and the effect of substrate of PARKIN turnover was also not known. This protocol provides a step‐by‐step guide on the use of the UbFluor probe to precisely quantitate changes in the activity of PARKIN in response to phosphorylation, allosteric activation by pUb, protein substrates, and activating structural mutations. These results pave the way to discover PARKIN activators and to precisely quantify the activity of other RBR E3s. © 2018 by John Wiley & Sons, Inc.